Anatomy of malice [computer viruses]. - Cass, S.
As in controlling the spread of real diseases, the key to effective defenses against computer viruses is to understand the cause and mechanism of infection, not to focus on the symptoms. A computer virus that erases a user's files may seem very different from one that merely prints out the occasional annoying message, but chances are, they both got into the system in a similar fashion. Malicious software falls, by and large, into three classes: Trojans, viruses, and worms. The way in which these viruses work is explained, as are methods to counteract them
Keywords: Trojans; Computer viruses; Malicious software; Viruses; Worms